Al0.5CoCrFeNi2 High Entropy Alloy Particle Reinforced AZ91 Magnesium Alloy-Based Composite Processed by Spark Plasma Sintering - Chun Chiu (MDPI AG, 2021)
In this study, AZ91 magnesium-alloy-based metal matrix composites (MMCs) reinforced with 10 wt% of Al0.5CoCrFeNi2 high-entropy alloy (HEA) particles and SiC particles were prepared by a spark plasma sintering (SPS) process at 300 °C. The effects of reinforcements on the microstructure and mechanical properties of AZ91-based MMCs were studied. The results showed that AZ91–HEA composite consisted of α-Mg, Mg17Al12 and FCC phases. No interfacial reaction layer was observed between HEA particles and the Mg matrix. After adding HEA into AZ91, the compressive yield strength (C.Y.S) of the AZ91–HEA composite increased by 17% without degradation of failure strain. In addition, the increment in C.Y.S brought by HEA was comparable to that contributed by commonly used SiC reinforcement (15%). A relatively low porosity in the composite and enhanced interfacial bonding between the α-Mg matrix and HEA particles make HEA a potential reinforcement material in MMCs.